Biologic therapies for juvenile idiopathic arthritis-associated uveitis - Dini, Gianluca; Dell’Isola, Giovanni Battista; Beccasio, Alfredo; Di Cara, Giuseppe; Verrotti, Alberto; Cagini, Carlo (Frontiers in Ophthalmology, 2022)
Juvenile idiopathic arthritis (JIA) is the most frequent rheumatic disease of childhood and uveitis is its most common extra-articular manifestation. JIA-associated uveitis (JIA-U) is one of the main causes of visual impairment in children and represents a major challenge for pediatrician and ophthalmologist, due to its insidious onset and sight-threatening complications. Topical glucocorticoids are the first line of treatment, followed by conventional disease-modifying anti-rheumatic drugs (DMARDs), usually methotrexate (MTX). In recent years, new biological drugs targeting specific molecules involved in disease pathogenesis, have significantly improved the prognosis of the disease, especially for cases refractory to conventional therapies. In this review we discuss the role of biological agents in JIA-U, focusing on cytokine blockers and cell-targeted therapies aimed to control ocular inflammation.